Green Economy: Evaluation of Malaysian Company Environmental Sustainability - Bakar, Nor'Aznin Abu; Abdullah, Hussin; Ibrahim, Fatimah Wati; Jali, Mohd Razani Mohd (International Journal of Energy Economics and Policy, 2017)
This paper examines the level of environmental sustainability in Malaysia. Lack of environmental improvements is still in the debate on sustainable development. Malaysia has moved to the manufacturing industry in recent years, but has a detrimental effect on the environment due to the increase in pollution, waste and the use of natural resources rapidly. The methodology used in this paper is based on ordinary least squares (OLS) estimation. The findings showed that the majority of the company's surveyed sample showed an increase in the understanding of their energy consumption, while other companies only invest to improve energy use because of legal compliance. In addition, the majority of companies to invest in the recycling and reuse of materials, the environmental friendly technology, internal training on green economy, the rest of the electorate and the purchase and use of materials with less impact simply because they believe that investment to ensure the preservation of nature around. Companies are concerned about the potential impact on the environment when they are aware of new products and services. It is also an indicator of a successful environmental sustainability in Malaysia based on the responses are analysed from a variety of high technology-based companies operating in Kedah, Malaysia. Keywords: Green economy; environmental sustainability, Malaysian company JEL Classifications: Q56, Q58